AUTOMATIC DETECTION OF MASSES FROM MAMMOGRAPHIC IMAGES VIA ARTIFICIAL INTELLIGENCE TECHNIQUES - AZLAN, NUR AAINAA NADIRAH (2021)
Breast cancer refers to the presence of abnormal cells in human breast tissue, which threaten human life after lung cancer